The two main endoproteases present in dark-induced senescent wheat leaves are distinct subtilisin-like proteases - Roberts, Irma (2006)
We have previously reported the occurrence of two serine endoproteases (referred as P1 and P2) in dark-induced senescent wheat (Triticum aestivum L.) leaves. P1 enzyme was already purified and identified as a subtilisin-like serine endoprotease. In this paper, we demonstrate by Western blot analysis of extracts obtained from dark-induced senescent leaves that an antiserum raised against P1 was able to recognise a second protein band of 78 kDa which corresponded to P2 activity. This result suggested that both enzymes must be structurally related. Therefore, we purified and characterized P2 activity. Its biochemical and physical properties (inhibition by chymostatin and PMSF, broad pH range of activity, thermostability and ability to hydrolyse Suc-AAPF-pNA) allowed its classification as chymotripsin-like protease. Samples of purified P1 and P2 were submitted to MALDI-TOF mass spectrometry analysis. Comparison of the peptide maps obtained clearly showed that P1 and P2 do not share peptides in common, although P2 was also identified as a subtilisin-like serine protease. Western blot analysis demonstrated that P1 was induced in non-detached dark-induced senescent leaves but was not detectable in senescent leaves promoted by nitrogen (N) deprivation. In contrast, P2 was already present in non-senescent leaves and its expression increased by darkness as well as by N starvation. These results indicate that, despite their biochemical and structural similarities, both enzymes are probably involved in different physiological roles.